Global geopolitical risk and industrial tail risk in the Chinese stock market: a quantile-on-quantile connectedness approach - Li, Jing; Li, Yunzhong; Lai, Fujun; Li, An (Frontiers in Physics, 2025)
Global geopolitical risk (GPR) has increasingly become a pivotal driver of financial market volatility, understanding the impact of GPR on market tail risk is crucial, particularly as traditional models often overlook the complex, nonlinear dynamics exacerbated by geopolitical shocks. This study offers an in-depth examination of the quantile-dependent spillover connectedness between GPR and the tail risk of 18 industries in the Chinese stock market. By using a quantile-on-quantile (QQ) connectedness approach, we investigate how shocks at varying quantiles propagate through the system, thereby uncovering nonlinear dynamics often obscured by traditional mean-variance models. Our findings reveal a distinct “U-shaped” quantile dependence, where extreme quantiles (5% and 95%) exhibit significantly heightened sensitivity to GPR compared to mid-range quantiles. Additionally, a net directional analysis demonstrates that industries with global integration or resource intensity (such as Manufacturing, Mining, and IT) typically serve as net risk receivers during geopolitical turbulence, while certain sectors (notably Finance) may act as net risk senders under specific conditions. A dynamic connectedness analysis further indicates that pivotal geopolitical events, including the 2018 China-U.S. trade war, the COVID-19 pandemic and the 2022 Russia-Ukraine conflict, act as junctures that intensify tail risk transmission. Collectively, these insights emphasize the necessity of quantile-specific risk monitoring and underscore the value of tailored policy interventions to mitigate severe downside risks amid escalating global uncertainties.